Interferensi Dialek Lokal terhadap Pembelajaran Bahasa Indonesia di Sekolah Dasar - Fathiya Desnika; Adrias, Adrias; Syam, Salmaini Safitri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the interference of local dialects in Indonesian language learning at the elementary school level. The research employs a qualitative method, utilizing data collection techniques such as participatory observation and in-depth interviews. The findings reveal that most students experience linguistic interference in various aspects. Several factors contribute to this interference, including the dominance of the Minangkabau dialect in daily life, the lack of emphasis on the differences between regional dialects and standard Indonesian in the learning process, and the limitations of teaching methods used by educators. Based on these findings, it is recommended that Indonesian language teachers implement more effective and contextual learning strategies. These strategies may include increasing students' awareness of the differences between regional dialects and standard Indonesian, employing interactive and engaging teaching methods, providing specialized training in pronunciation and sentence structure that aligns with Indonesian language rules, and conducting regular evaluations to adjust learning strategies according to students' needs. With a more adaptive and innovative approach, students are expected to acquire better proficiency in Indonesian and reduce the influence of local dialects in their learning process